Can clinical vignettes administered by mobile phone call be used to measure quality of contraceptive care practices in Malawi? - Elizabeth Hazel; Diwakar Mohan; Joanne Katz; Ephraim Chirwa; Patrick Msukwa; Melissa A. Marx (Journal of Global Health Reports)
# Background Accurate and timely measures of quality of contraceptive care are required for program improvement but can be expensive and time-consuming to implement in low- and middle-income countries (LMICs). Clinical vignettes (CLVs) measure quality knowledge and have been shown to be a valid proxy of provider quality practice in the United States, and may be administered via mobile-phone, making them an attractive cost-savings alternative to field assessments. This cross-sectional study aims to validate mobile-phone CLVs for measuring quality of contraceptive service provision using simulated, “mystery” clients as the gold standard.